Physico-Chemical Properties of Semi Refined Carrageenan (SRC) Kappaphycus alvarezii from Karimun, Riau Islands, Indonesia - Aidil Fadli Ilhamdy; Jumsurizal Jumsurizal; Wan Kirana Shabilla; Ginanjar Pratama (Jurnal Perikanan dan Kelautan, 2019)
Carrageenan is a non-fish fishery product derived from the extraction of red seaweed (Rhodophyceae) Kappaphycus alvarezii. It is generally used in the field of cosmetics industry, textiles, food, pharmaceutical, stabilizer and gel formation. The objective of this study was to determine the physico-chemical properties of semi refined carrageenan (SRC) on red seaweed (Kappaphycus alvarezii). The research phase included the preparation of raw materials for Kappaphycus alvarezii and making SRC, then followed by physico-chemical analysis, yield, moisture content, ash content, acid insoluble ash content, gel strength, viscosity, melting point, and cumulative point. The Physico-chemical SRC observations were yields of 24.80%, the water content of 19.20%, ash content of 16.34%, insoluble ash content in acid 0.31, the strength of gel 376.46 g/cm2, viscosity 139.47 cP, melting point 55.700C, graduation point 380C.